+0  
 
+1
162
1
avatar

The table shows values for functions  f(x) and  g(x)

What is the solution to  f(x)=g(x)

Select each correct answer 

x = -3

x = -2

x = -1

x = 0

x = 1

x = 2

x = 3

 

The functions   f(x)=−2x+2 and   g(x)=(1/3)x+1 are shown in the graph.

What are the solutions to  −2x+2=(1/3)x+1?

Select each correct answer 

-1

0

2

3

4

Guest Jan 9, 2018

Best Answer 

 #1
avatar+7336 
+1

1.

 

When   x = -2 ,   f(x) = 4   and   g(x) = 4   so when   x = -2 ,   f(x) = g(x) .

 

When   x = -1 ,   f(x) = 2   and   g(x) = 2   so when   x = -1 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 

 

2.

 

The solutions to   -2x + 2  =  (1/3)x + 1   are the solutions to  f(x) = g(x) .

 

When   x = -1 ,   f(x) = 4   and   g(x) = 4   so when   x = -1 ,   f(x) = g(x) .

 

When   x = 0 ,   f(x) = 2   and   g(x) = 2   so when   x = 0 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

hectictar  Jan 9, 2018
 #1
avatar+7336 
+1
Best Answer

1.

 

When   x = -2 ,   f(x) = 4   and   g(x) = 4   so when   x = -2 ,   f(x) = g(x) .

 

When   x = -1 ,   f(x) = 2   and   g(x) = 2   so when   x = -1 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

 

 

2.

 

The solutions to   -2x + 2  =  (1/3)x + 1   are the solutions to  f(x) = g(x) .

 

When   x = -1 ,   f(x) = 4   and   g(x) = 4   so when   x = -1 ,   f(x) = g(x) .

 

When   x = 0 ,   f(x) = 2   and   g(x) = 2   so when   x = 0 ,   f(x) = g(x) .

 

None of the other values for  x  make  f(x) = g(x) .

hectictar  Jan 9, 2018

22 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.